Papst Pius II. an Sultan Mehmet II.: Die Übersetzung der 'Epistola ad Mahumetem' durch Michael Christan - Wolf, Klaus; Göhler, Jonas (Veröffentlichungen des Grabmann-Institutes zur Erforschung der Mittelalterlichen Theologie und Philosophie, 2016)
For the first time, this book offers an edition of the Early High German translation of the tractate Epistola ad Mahumetem. The humanist Michael Christan translated this key work by Pope Pius II from the Latin original in the late 15th century. It describes the Pope’s offer of conversion to Sultan Mehmed II. This first edition thus serves to document the rising journalistic interest in Turkey in the waning 15th century.
Keywords: Quelle; Mittelhochdeutsch; Übersetzung; Pius <II., Papst> / Epistola ad Mahomatem; Christan, Michael; Geschichte 1461; Brief; Islam; Interreligiöser Dialog; Christentum; Mehmed <II., Osmanisches Reich, Sultan>; Pius <II., Papst>